"All Eyes on Me": A Qualitative Study of Parent and Patient Experiences of Multidisciplinary Care in Craniofacial Conditions. (October 2019) - Myhre, Anita; Agai, Mehri; Dundas, Ingrid; Feragen, Kristin Billaud
Objective: The present study investigated how adults with congenital craniofacial anomalies (CFAs) and parents experience the long-term and complex treatment offered by a multidisciplinary team (MDT). Design: Exploratory-descriptive qualitative study based on individual semistructured interviews. Setting: Centralized national follow-up and treatment of CFAs by a multidisciplinary craniofacial team from which participants were systematically recruited. Participants: The sample included 48 parents of children with CFAs and 16 adults with CFAs (N = 64). Results: In general, participants reported to be satisfied with the follow-up and treatment they received from the MDT. Still, some aspects of treatment were experienced as demanding such as the large number of health professionals present during the consultation and being the object of their scrutinizing attention. Health professionals' communication skills were described as central for participants' involvement in, and satisfaction with, treatment. Participants also expressed a need for more treatment-related information regarding future treatment. Conclusions: Findings could have implications for the organization of care for parents and patients with rare CFAs. The many advantages of MDTs also create unique challenges for patients and parents that need to be addressed. Patients and families should be prepared for the first consultation with the MDT. Health professionals should be aware of their communication style when interacting with patients and be aware of individual differences and needs regarding treatment-related experiences and expectations.